Validation of the FACT-G7 in patients with hematologic malignancies - Du, Xinwen; Mao, Ling; Leng, Yamei; Chen, Fengjiao (Frontiers in Oncology, 2023)
Background It is essential to evaluate the quality of life in patients with hematologic malignancies to reflect the therapeutic effect and prognosis, but lengthy assessments are often burdensome. The 7-Item Functional Assessment of Cancer Therapy-General (FACT-G7) is a brief, easy, and rapid index for evaluating quality of life. Nevertheless, there is no report about its application in Chinese patients with hematologic malignancies. Objective The purpose of this study was to validate the Chinese version of the FACT-G7 for patients with hematologic malignancies. Methods This study is a cross-sectional study. A total of 855 patients with hematologic malignancies completed the Functional Assessment of Cancer Therapy-General (FACT-G) and were scored the Eastern Cooperative Oncology Group Performance Status (ECOG-PS) by nurses. Cronbach’s alpha, confirmatory factor analyses, Pearson’s correlation, and one-way analysis of variance were conducted to evaluate internal consistent reliability, structural validity and concurrent validity. Results The FACT-G7 showed acceptable internal consistency, as indicated by a Cronbach’s alpha of 0.73. The confirmatory factor analyses test for single-factor model fit for the FACT-G7 scale was almost adequate. The satisfactory correlations between the FACT-G7 and the FACT-G and its subscales, and ECOG-PS groups differed in FACT-G7 scores demonstrating concurrent validity. Conclusion This study suggested that the Chinese version of the FACT-G7 provides a useful and rapid measure for assessing quality of life in Chinese patients with hematologic malignancies, which providing a reference for further evaluation and care.